The role and mechanism of gut microbiota-derived short-chain fatty in the prevention and treatment of diabetic kidney disease - Tao, Pengyu; Ji, Jing; Wang, Qian; Cui, Mengmeng; Cao, Mingfeng; Xu, Yuzhen (Frontiers in Immunology, 2022)
Diabetic kidney disease (DKD), an emerging global health issue, is one of the most severe microvascular complications derived from diabetes and a primary pathology contributing to end-stage renal disease. The currently available treatment provides only symptomatic relief and has failed to delay the progression of DKD into chronic kidney disease. Recently, multiple studies have proposed a strong link between intestinal dysbiosis and the occurrence of DKD. The gut microbiota-derived short-chain fatty acids (SCFAs) capable of regulating inflammation, oxidative stress, fibrosis, and energy metabolism have been considered versatile players in the prevention and treatment of DKD. However, the underlying molecular mechanism of the intervention of the gut microbiota–kidney axis in the development of DKD still remains to be explored. This review provides insight into the contributory role of gut microbiota-derived SCFAs in DKD.